PENGEMBANGAN MEDIA PEMBELAJARAN PROTOTYPE LIFT BERBASIS PLC PADA MATA PELAJARAN INSTALASI MOTOR LISTRIK KELAS XII TITL DI SMK NEGERI 14 MEDAN - Kevin Boijogy Batubara; Wanapri Pangaribuan (Universitas Negeri Medan, 2023)
Abstract This study aims: (1) To find out students' responses to learning media for lift prototypes based on PLC Omron type CPM1A for electric motor installation subjects on Forward-Reverse electric motor control material for class XII TITL SMK Negeri 14 Medan (2) To find out the results from developing learning media by designing learning media for prototype lifts based on PLC type Omron type CPM1A on electric motor installation subjects for class XII SMK Negeri 14 Medan, and (3) To determine the feasibility of learning media for prototype lifts based on PLC type Omron type CPM1A for eyes electric motor installation lessons class XII SMK Negeri 14 Medan odd semester 2022/2023 academic year. The type of research used is Research and Development (R&D) with the ADDIE research model. The ADDIE research model includes five stages, namely the first analysis which includes needs analysis, the second design, namely designing mechanical, electrical and wiring as well as program design for learning media for prototype elevators, the third development, namely developing learning media by designing and building a three-floor PLC-based elevator prototype that has been designed to do a feasibility test in order to get input from media experts and material experts, the fourth is implementation, namely implementing the product to get responses from users (students) to the prototype lift learning media that has been developed, the fifth evaluation, namely evaluating modules based on some input from experts and responses user. The instruments used in this study were due diligence questionnaires and user response questionnaires. The validity used is based on the opinions of two material experts and two media experts. The results of this study can be seen: (1) This development research produces a product in the form of a PLC-based lift prototype learning media for the class XII TITL electric motor installation subject at SMK Negeri 14 Medan. (2) The feasibility of the prototype elevator learning media in terms of material experts gets a score of 87.50% of the maximum percentage of 100% and is categorized as